1996
DOI: 10.1103/physrevlett.76.3456
|View full text |Cite
|
Sign up to set email alerts
|

Rifts in Spreading Wax Layers

Abstract: We report experimental results on the rift formation between two freezing wax plates. The plates were pulled apart with constant velocity, while floating on the melt, in a way akin to the tectonic plates of the earth's crust. At slow spreading rates, a rift, initially perpendicular to the spreading direction, was found to be stable, while above a critical spreading rate a "spiky" rift with fracture zones almost parallel to the spreading direction developed. At yet higher spreading rates a second transition fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…This wax gave birth to the different regimes shown in Figure 55 (Ragnarsson et al, 1996), but the orthogonal transform faults observed by Brune (1972, 1975) were never observed. In the first case (Shell Wax 120), the solid layer could be divided in two regions because the paraffin wax undergoes a solid-solid phase transition: a colder phase, hard and brittle, where strain is mostly accomodated by crack formation during extension; and a warmer ductile phase, where strain is accomodated primarily by viscous flow.…”
Section: Morphology Of Ridgesmentioning
confidence: 85%
See 2 more Smart Citations
“…This wax gave birth to the different regimes shown in Figure 55 (Ragnarsson et al, 1996), but the orthogonal transform faults observed by Brune (1972, 1975) were never observed. In the first case (Shell Wax 120), the solid layer could be divided in two regions because the paraffin wax undergoes a solid-solid phase transition: a colder phase, hard and brittle, where strain is mostly accomodated by crack formation during extension; and a warmer ductile phase, where strain is accomodated primarily by viscous flow.…”
Section: Morphology Of Ridgesmentioning
confidence: 85%
“…Ridge morphology has been studied using paraffin wax as an analog mantle material: solid wax simulates brittle mantle and molten material simulates the region that deforms as a viscous fluid Brune, 1972, 1975;Ragnarsson et al, 1996). The molten wax was frozen at the surface by a flow of cold air.…”
Section: Morphology Of Ridgesmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental and theoretical modeling of the MOR mechanism has thus recently gained its wide acceptance as an effective alternative approach. Analog models have been used extensively, utilizing mainly wax of different variety (Katz et al, 2005;O'bryan et al, 1975;Oldenburg and Brune, 1975;Ragnarsson et al, 1996) and other materials, such as sand-silicone (Dauteuil et al, 2002), sand-PDMS (Marques et al, 2007), and silicone (Tentler and Acocell, 2010). Unfortunately, these analog experiments did not couple the process of magmatic upwelling with the segmentation mechanism.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 98%
“…These walls, subjected to electric and magnetic fields, can exhibit a zig-zag instability [13][14][15]. This type of instability is a universal phenomenon, which is observed in various * iandrade@ing.uchile.cl † marcel@dfi.uchile.cl ‡ vodent@ing.uchile.cl physical contexts such as in microwrinkle grooves [16], gas discharge systems [17], crystals growth [18], rifts in the spreading wax layer [19], the chevron layer structure of smectic liquid crystals [20], and nematic liquid crystal samples subjected to a temperature gradient [21] or a confinement configuration [22].…”
Section: Introductionmentioning
confidence: 98%